Hubungan Antara Pengetahuan Seksualitas dengan Sikap Terhadap Perilaku Seks Pranikah pada Remaja di Forum Anak (FAN) Kota Semarang - Erma Yuliana Septi (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
Premarital sexual behavior among adolescents is an increasingly worrying social phenomenon. Data from various institutions show an increasing number of adolescents engaging in extramarital sexual relations, which has an impact on the risk of unwanted pregnancy, sexually transmitted diseases, and psychological problems. One factor that influences adolescents' tendencies towards such behavior is their level of knowledge about sexuality. Lack of knowledge can cause adolescents to have a permissive attitude towards unhealthy sexual behavior. This study aims to determine the relationship between sexuality knowledge and attitudes towards premarital sexual behavior among adolescents in the Semarang City Children's Forum (FAN). This study was conducted using a quantitative research type with a correlational research design. The population in this study were all 43 members of the Semarang City Children's Forum (FAN). The sample used in this study was the entire population, namely 43 people. Sampling in this study used a saturated sampling technique. The data collection technique used a Guttman scale, namely sexuality knowledge, and a Likert scale, namely attitudes towards premarital sexual behavior. Based on the Spearman rho hypothesis test, the significance value (2-tailed) was 0.007 < 0.05, and the calculated r value > r table, namely 0.402 > 0.301, indicating a positive correlation. This means that the higher a person's level of knowledge about sexuality, the higher their positive attitude in rejecting premarital sexual behavior.